The school of greatness : a real-world guide for living bigger, loving deeper, and leaving a legacy - Howes, Lewis, 1983- (Rodale, 2015)
"When a career-ending injury left elite athlete and professional football player Lewis Howes out of work and living on his sister's couch, he decided he needed to make a change for the better. He started by reaching out to people he admired, searching for mentors, and applying his past coaches' advice from sports to life off the field. Lewis did more than bounce back: He built a multimillion-dollar online business and is now a sought-after business coach, speaker, and podcast host. In The School of Greatness, Howes shares the essential tips and habits he gathered in interviewing "the greats" on his wildly popular podcast of the same name. In discussion with people like Olympic gold medalist Shawn Johnson and Pencils of Promise CEO Adam Braun, Howes figured out that greatness is unearthed and cultivated from within. The masters of greatness are not successful because they got lucky or are innately more talented, but because they applied specific habits and tools to embrace and overcome adversity in their lives. A framework for personal development, The School of Greatness gives you the tools, knowledge, and actionable resources you need to reach your potential. Howes anchors each chapter with a specific lesson he culled from his greatness "professors" and his own experiences to teach you how to create a vision, develop hustle, and use dedication, mindfulness, joy, and love to reach goals. His lessons and practical exercises prove that anyone is capable of achieving success and that we can all strive for greatness in our everyday lives."--provided by publisher.